Ethnomathematical Connections of Indramayu Traditional Boat Forms: Implications For Institutionalization School Geometry Concept - Nurafifah, Luthfiyati; Gunadi, Farid; Sudirman, Sudirman; Wahyudin, Wahyudin (Universitas Wiralodra, 2024)
artifacts, and so on. However, there still needs to be more emphasis on the connection between traditional boat building and mathematics. Therefore, this article aims to characterize the ethnomathematics connections built from the traditional Indramayu boat shape. Theoretically, this research is based on ethnomathematics, ethnomathematics connections, and Universal Activity. The research approach used is qualitative by using an ethnographic design. This article's research object is the form of traditional boats in Indramayu—the research data obtained from preliminary studies, observations, interviews, and documentation. Interviews were conducted with three people, namely two builders and crew members (Ship's Crew). Based on the results of the study, it was found that the ethnomathematics connection to traditional boats can be seen in the forms of boat buildings and the accessories that complement them, such as the lunas, haluan, lambung, kemudi, hatch, and storage area. Institutionalizing the parts of the boat can represent the concepts of plane and spatial geometry. Therefore, the implications of this article can enrich students' starting points for learning mathematics and facilitate students' understanding of abstract mathematics using the context of society's culture.